An Entropic Scheme for an Angular Moment Model for the Classical Fokker-Planck-Landau Equation of Electrons (Communications in Computational Physics, 2018)
In plasma physics domain, the electron transport is described with the Fokker-Planck-Landau equation. The direct numerical solution of the kinetic equation is usually intractable due to the large number of independent variables. That is why wepropose in this paper a new model whose derivation is based on an angular closurein the phase space and retains only the energy of particles as kinetic dimension. Tofind a solution compatible with physics conditions, the closure of the moment system is obtained under a minimum entropy principle. This model is proved to satisfythe fundamental properties like a H theorem. Moreover, an entropic discretization inthe velocity variable is proposed on the semi-discrete model. Finally, we validate onnumerical test cases the fundamental properties of the full discrete model.